Biogeographical patterns and determinants of invasion by forest pathogens in Europe. Issue 1 (11th October 2012) - Santini, A.; Ghelardini, L.; De Pace, C.; Desprez‐Loustau, M. L.; Capretti, P.; Chandelier, A.; Cech, T.; Chira, D.; Diamandis, S.; Gaitniekis, T.; Hantula, J.; Holdenrieder, O.; et al.
Summary: A large database of invasive forest pathogens (IFPs) was developed to investigate the patterns and determinants of invasion in Europe. Detailed taxonomic and biological information on the invasive species was combined with country‐specific data on land use, climate, and the time since invasion to identify the determinants of invasiveness, and to differentiate the class of environments which share territorial and climate features associated with a susceptibility to invasion. IFPs increased exponentially in the last four decades. Until 1919, IFPs already present moved across Europe. Then, new IFPs were introduced mainly from North America, and recently from Asia. Hybrid pathogens also appeared. Countries with a wider range of environments, higher human impact or international trade hosted more IFPs. Rainfall influenced the diffusion rates. Environmental conditions of the new and original ranges and systematic and ecological attributes affected invasiveness. Further spread of established IFPs is expected in countries that have experienced commercial isolation in the recent past. Densely populated countries with high environmental diversity may be the weakest links in attempts to prevent new arrivals. Tight coordination of actions against new arrivals is needed. Eradication seems impossible, and prevention seems the only reliable measure, although this will be difficult in the face of global mobility. Abstract : See also the Commentary by Britton and Liebhold